2016
DOI: 10.1111/nuf.12190
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Patients of the Millennial Generation: Considerations for Nurses

Abstract: Much has been written about teaching students of the Millennial Generation (those born between the years 1980 and 2000) and about intergenerational dynamics in the healthcare workforce. However, little can be found in the literature regarding generation-specific nursing care of Millennial patients. This article presents six categories of considerations for nurses caring for patients of the Millennial Generation based on the characteristics, attitudes, and values that have influenced them as well as the healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
4
0
6
Order By: Relevance
“…Each successive generation is shaped and created by significant societal changes. Generational trends indicate an ongoing evolution of a population that is better educated, increasingly diverse, and comfortably immersed in the digital world [15]. It is important to be sensitive to the effects of cosmetic and reconstructive procedures like otoplasty on health-related quality of life across generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each successive generation is shaped and created by significant societal changes. Generational trends indicate an ongoing evolution of a population that is better educated, increasingly diverse, and comfortably immersed in the digital world [15]. It is important to be sensitive to the effects of cosmetic and reconstructive procedures like otoplasty on health-related quality of life across generations.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the confidence interval analysis (Figure 4) suggest that the GBI score of the Z generation is significantly higher than that of the Y generation. Being aware of health issues specific to these generations is the first step in effectively assisting young generation patients [15]. Limitations of the study include the retrospective design, which excluded factors such as social status, environment, education level, and others, apart from age, from the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Apreendeu-se que a população dos artigos analisados, publicados entre 2006 e 2020, pode ser composta por pessoas nascidas entre as décadas 1990 e 2010, integrando um contexto histórico "milennial", a chamada Geração Digital ou Geração Y. Advindos da era tecnológica, têm peculiaridades nas relações afetivas, familiares, de saúde, educação, entre outras. 35 Com facilidade para o acesso à informação -mas nem sempre de boa qualidade -, os adolescentes podem ser suscetíveis a comportamentos de risco, como os elencados nessa categoria (Figura 2). Por outro lado, utilizar as próprias ferramentas digitais para interagir e promover saúde desvelando temas diversos pode ser uma alternativa relevante, já que considera a vivência e a habilidade que essa geração tem com as tecnologias.…”
Section: Componente: Características E Experiências Individuaisunclassified
“…This finding is congruent with Swanson (2015), who suggested that the ultimate goal of caring is to enable clients to achieve well-being. In today's healthcare, the use of technology constitutes consideration for caring for patients of the millennial generation (Johanson, 2016). Besides, most of today's nurses are part of this millennial generation.…”
Section: The Drivers For Technological Developmentmentioning
confidence: 99%